PENGARUH PERSON-JOB FIT DAN PERCEIVED SUPERVISOR SUPPORT PADA ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN PEMEDIASI KEPUASAN KERJA PADA PT MEGA JAYA LOGAM KLATEN - Buchory, Hasan; Kurniawan, Ignatius Soni; Lysander, Mohammad Ahyar Syafwan (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
This study aims to examine the influence of the variables person-job fit (P-JF), perceived supervisor support (PSS), and job satisfaction (KK) mediated by organizational citizenship behavior (OCB). The population in this study were employees of PT Mega Jaya Logam Klaten, with a sample size of 50 respondents. Data were collected through direct surveys and then processed using multiple linear regression analysis. The results showed that P-JF had a positive and significant effect on job satisfaction. PSS has no significant effect on PSS. P-JF, PSS, and KK have no significant effect on OCB.